2020
DOI: 10.3390/antiox9040285
|View full text |Cite
|
Sign up to set email alerts
|

Cyanidin Chloride Induces Apoptosis by Inhibiting NF-κB Signaling through Activation of Nrf2 in Colorectal Cancer Cells

Abstract: Colorectal cancer (CRC) is the third most common cancer worldwide and a leading cause of cancer-related deaths in developed countries. Anthocyanins are a class of flavonoids, widely distributed in food, exhibiting important biological effects. Cyanidin chloride (CyCl) is the common type of anthocyanin with antioxidative and anti-inflammatory potential. The present study aimed to investigate the molecular mechanisms underlying the chemotherapeutic effects of CyCl in colorectal cancer cells. We found that CyCl t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…The Nrf2 signaling pathway is a key component of the body’s basic defense system against oxidative and electrophilic damage [ 72 ]. Anthocyanins activate a common ARE in the upstream region of their antioxidant genes, regulated by multiple transcription factors, including Nrf2 [ 73 ]. CpG sites in the Nrf promotor region are demethylated as a result of delphinidin activation of Nrf2/ARE, as evidenced by decreased expression of class I/II histone deacetylases and DNA methyltransferases 1 and 3a (DNMT1/3a) ( Table 2 ) [ 26 ].…”
Section: Delphinidin and Anticancer Activitiesmentioning
confidence: 99%
“…The Nrf2 signaling pathway is a key component of the body’s basic defense system against oxidative and electrophilic damage [ 72 ]. Anthocyanins activate a common ARE in the upstream region of their antioxidant genes, regulated by multiple transcription factors, including Nrf2 [ 73 ]. CpG sites in the Nrf promotor region are demethylated as a result of delphinidin activation of Nrf2/ARE, as evidenced by decreased expression of class I/II histone deacetylases and DNA methyltransferases 1 and 3a (DNMT1/3a) ( Table 2 ) [ 26 ].…”
Section: Delphinidin and Anticancer Activitiesmentioning
confidence: 99%
“…In addition, it was found that xanthone can act as vasodilator [44]. Next, cyanin, also known as cyanin chloride or cyanidin-3,5-di-O-glucoside, was reported to induce apoptosis by inhibiting NF-κB signaling through activation of Nrf2 in colorectal cancer cells [45]. Flavocommelin, which is one of the components identified in Commelina communis [46] and was reported to reduce lung damage in influenza virus-infected mice [47].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the two most upregulated avonoids are isorhamnetin-o-gallate and cyanidin chloride, the former is a avonol and belongs to the group of plant secondary metabolites known as avonoids, which have been reported for many biological activities such as antioxidant, anticancer, antimicrobial and anti-in ammatory effects [24] . The latter is one of the most abundant types of anthocyanins and has been shown to have antioxidant properties inhibiting nitric oxide production in many studies [25,26] . Moreover, sinapine was signi cantly upregulated in Peking samples, which led to signi cant improvements in energy, lipid and glucose metabolism in animal models [27][28][29][30] , indicating that sinapine may be an important alkaloid in D. o cinale cultivated in Beijing.…”
Section: Discussionmentioning
confidence: 99%